The income measurement properties of two crude inflation-accounting models - Wim R. Gevers (South African Journal of Business Management, 1994)
Although the inflation rate in South Africa has been high over an extended period of time, accounting for the effect of inflation has not progressed further than Guideline AC201 of the South African Institute of Chartered Accountants. Research in the United States of America and the United Kingdom on the value of published inflation-accounting data has yielded little evidence of information content. Similar findings were obtained in South Africa based on estimated inflation-accounting data. Evidence of the income measurement properties of inflation-adjusted data in the USA has, however, been documented. In this article the income measurement properties of two simplified or crude inflation-accounting models are determined for industrial companies listed on the Johannesburg Stock Exchange (JSE). It is found that the historic cost income generally behaves as expected, but that the inflation adjustments to income contain little or no income measurement properties. The little positive evidence found points to the desirability of the disclosure of holding gains information.
Keywords: 650